Christian-Muslim relations: a look backwards and a look forwards - Goddard, Hugh (Islam and Christian-Muslim relations, 2000)
At a significant moment in the calendar of one of the two concerned traditions, as the Christian community enters the second millennium of its history, this article looks back over the history of the relationship between Christians and Muslims and selects some examples of defining moments in the relationship. These examples illustrate the wide variety of attitudes towards and perceptions of the other which are evident in history. The article then attempts to look forward and outline some features which are desirable for the future study of Christian-Muslim relations.